Trends in pharmaceutical marketing and branding research: a bibliometric analysis (2009–2023) - Thamburaj Anthuvan; Kajal Maheshwari; Raghunath Dantu (IIM Ranchi Journal of Management Studies)
Purpose – This study conducts a comprehensive bibliometric analysis of pharmaceutical marketing and branding research, focusing on the transformative period of the last 15 years (2009–2023), particularly during and after the COVID-19 pandemic. The purpose of this analysis is to highlight key shifts and trends in the field over this period. Design/methodology/approach – This study examined 329 research papers sourced from JSTOR and PubMed. It explores the evolution of the field, emphasizing significant shifts and trends. Findings – The analysis identified 2009 and 2014 as pivotal years for research activity, with The British Medical Journal and BioMed Central emerging as key publication platforms. Contributions from the USA, led by authors like Joel Lexchin, were particularly notable. The study also highlighted a shift toward AI-driven marketing, digital transformation and personalized medicine, especially in the post-COVID-19 period (2020 onwards). Co-authorship networks and keyword analysis emphasized the growing focus on regulatory compliance, patient engagement and the integration of digital tools in pharmaceutical marketing. Originality/value – This study charts the historical and current state of pharmaceutical marketing and branding and sets the foundation for future research, emphasizing the increasing role of digitalization and AI.